Clinical significance of anatomical urethral length on stress urinary incontinence women - Shin YS; You JH; On JW; Kim MK (Dove Medical Press, 2018)
Yu Seob Shin, Jae Hyung You, Ji Won On, Myung Ki Kim Department of Urology, Chonbuk National University Medical School, Research Institute of Clinical Medicine of Chonbuk National University – Biomedical Research Institute of Chonbuk National University Hospital, Jeonju, Republic of Korea Objective: To evaluate the association between the length of the female urethra and urodynamic study (UDS) parameters in patients presenting with stress urinary incontinence (SUI).Patients and methods: We retrospectively enrolled 391 women who underwent a transobturator adjustable tape sling implantation for the management of SUI between April 2009 and March 2016. All patients underwent a physical examination and UDS. Filling cystometry data that were evaluated included the Valsalva leak point pressure, and the cough leak point pressure. The maximal urethral closure pressure, the functional urethral length (FUL), and the length of the continence zone (LCZ) were measured using the urethral profile obtained from the UDS. The anatomical urethral length (AUL) was measured intraoperatively using a Foley catheter. We calculated the LCZ/FUL ratio to determine the anatomical continence length for this study.Results: We noted that 299 patients completed the study. The mean AUL was 26.25±3.59 mm. The mean FUL and LCZ were 41.37±15.05 mm and 24.15±13.90 mm, respectively. The mean LCZ/FUL was 0.57±0.19. Using the Pearson correlation coefficient, we observed that the AUL showed a correlation with the FUL (0.168, P=0.034), the LCZ (0.212, P=0.007), the LCZ/FUL ratio (0.190, P=0.016), the Valsalva leak point pressure (0.223, P=0.005), the cough leak point pressure (0.215, P=0.006), and the maximal urethral closure pressure (0.178, P=0.043).Conclusion: Our results show that the AUL in women is associated with UDS parameters relating to SUI. Keywords: stress urinary incontinence, urethral length, urodynamics, women